Captive lives : looking for Tambo and his companions : exhibition background information kit - National Library of Australia. Education Services ([Canberra] : National Library of Australia, 1998)
Topic sheets are titled: Curriculum links; Brief introduction to cross-cultural awareness; Australia's Indigenous cultures ' We have survived'; Early British contacts 1770 to settlement; The North Queensland frontier; Peoples of the Carpet Snake; Stereotypes; From human beings to human curiosities; The Aboriginal Protection and Restriction of the Sale of Opium Act 1897; The return of Tambo.
"Curated by Roslyn Poignant ; community consultation coordinators: Walter Palm Island, Manbarra ; Josephine Geia, Palm Island ; and Ernest Grant, Girringun."
Title from cover page.
"A travelling exhibition of the National Library of Australia."
Keywords: Prisoners, Aboriginal Australian -- United States -- History; Prisoners, Aboriginal Australian -- History; Aboriginal Australians -- United States -- History; Cultural heritage - Repatriation - Human remains; Race relations - Violent; Education - Teaching - Materials; Race relations - Racism - Stereotyping; Employment - Conditions - Slavery and indentured labour; Australia -- History -- 1788-1900.; Palm Island (NE Qld SE55-10)